SCHOOL ZONE POLICY SYSTEM EVALUATION AND ITS EFFECTS TOWARDS INDONESIAN EDUCATION - Ricky Erlangga; Fadilla Purnia Putri; Aisyah Arij Dhoifah; Mia Ayu Damayanti; Windra Tunggawijaya; Fatih Akbar Rafsanjani (PEDAGOGIA, 2023)
The inequality of education in various regions in Indonesia is one of the problems that are still being resolved. In 2018, the government launched a policy for Accepting New Students at the Kindergarten to High School level called the Zoning System policy with the aim of realizing an equitable education. Every rule or policy that has been successfully implemented must be evaluated in order to know the effectiveness and efficiency in achieving the expected goals. The purpose of writing this article is to make it easier for readers to find out the evaluation of zoning system policies in various regions. The writing method is in the form of Systematic Literature Review (SLR) or structured article reviews so that later various strategies will be found from several similar research results. So that several evaluation points were obtained for the zoning system policy, including, (1) Learning became less qualified because the number of students was not comparable with the facilities and infrastructure available; (2) The decline in the quality of students because there is no standardization of acceptance; (3) Parents' lack of understanding of the essence of the zoning system due to lack of socialization.